Роль чорносотенного СРН в ускладненні міжнаціональних відносин на Волині у 1906-1914 pp. - Цецик, Я.П. (Історичний архів. Наукові студії, 2015)
З’ясовано роль чорносотенного СРН у загостренні міжнаціональних взаємовідносин на Волині на початку ХХ ст. Досліджено антипольський та антиєврейський напрями діяльності цієї політичної структури. Проаналізовано роль Російської православної церкви у поширенні ідеології чорносотенців на Волині. Выяснена роль черносотенного СРН в обострении межнациональных взаимоотношений на Волыни в начале ХХ в. Исследованы антипольский и антиеврейский направления деятельности этой политической структуры. Проанализировано роль Русской православной церкви в распространении идеологии черносотенцев на Волыни. On the basis of primary sources and scholarly works analyzed the negative role of the Russian reactionary NRF complication in international relations in the Volyn province in 1906–1914. Particular attention is paid to the
elucidation of the structure of this political effort to discredit in the eyes of the general population of Polish Catholics and Jews. Determining in relation to members of other ethnic groups from the Russian Black Hundreds were their denominational affiliation and nationality. For anti-Catholic activities that rapidly developed in the region of the Black Hundreds began after the revolution in 1905 and although the Volyn large anti-government protests did not occur, however, much of the province’s population belonged negatively to the Russian authorities. It should be noted that the Poles at that time were the third largest ethnic group of the province’s population, but accounted for most of the landowners in the region, and efforts by Russian authorities to weaken the Polish land ownership on the Right Bank Ukraine did not give the desired results for the government. Another factor that influenced the situation was a sharp increase in the number of Catholics in Volyn in the study period. This was not only due to the natives of the Kingdom of Poland, but also due to return to the Catholic faith of Poles after the defeat of the Polish uprising accepted the Orthodox faith.
The attack on the Polish population of Volyn, accompanied by involvement in the case of the Orthodox clergy from the Black Hundreds, received an adequate response on the part of the Polish population. Those unfounded allegations of all the "deadly sins" that demagogic advanced Russian Black Hundreds Poles and priests complicated internal situation in the region intensified inter-confessional conflict between Catholics and Orthodox, which by the way at that time was provoked by Russian reactionary clergy.
Relationships were difficult between Jews and the Black Hundreds. Blatant anti-Semitic propaganda representatives of the political forces led to the aggravation of Russian-Jewish relations in Volyn in the early twentieth century. This position is for Jews on their part was due to the support of these ideas and authorities. Constant pressure and libel against Jews also contributed complication of Russian-Jewish relations in the region.
These activities contributed to NRF reactionary aggravation of interethnic relations in Volyn before World War I.